2023
DOI: 10.1002/apj.2997
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on active droplet generation governed by pulsatile continuous‐phase flow

Yanyin Zhang,
Jiamin Wang,
Jiawei Wu
et al.

Abstract: Precise control on the droplet generation is an important issue for the application of droplet microfluidics. Passive formation of droplets depends on multiparameters. The droplet size and generation frequency highly correlate to each other, raising the control difficulty. In comparison, the active method through external perturbations is more flexible. In this work, the droplet generation governed by pulsatile continuous‐phase flow is numerically studied. The effects of the pulsation amplitude and frequency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…From above discussions, the droplet ejection technology still has much room for improvement regarding its control flexibility and application universality. In our previous studies, we have demonstrated that external perturbation is a straightforward and efficient method for active droplet generation in pipe flows. In both the water–oil and liquid–air systems, flexible generation of liquid droplets or bubbles can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…From above discussions, the droplet ejection technology still has much room for improvement regarding its control flexibility and application universality. In our previous studies, we have demonstrated that external perturbation is a straightforward and efficient method for active droplet generation in pipe flows. In both the water–oil and liquid–air systems, flexible generation of liquid droplets or bubbles can be achieved.…”
Section: Introductionmentioning
confidence: 99%